Exploring Elements of Naturalism in Hardy’s The Mayor of Casterbridge - Ishaq, Ramsha; Razaq, Abdur; Sardaraz, Khan; Khan, Dr. Nijat Ullah (The journal of contemporary issues in business and government, 2021)
This paper explores the elements of naturalism in Hardy’s The Mayor of Casterbridge (2004) from Emile Zola’s dimension of naturalism. The major issue of the paper is that hereditary and environment control human’s actions. It also investigates how these two elements change our destiny and course of life. Emile Zola’s ideas have been used as tools for collecting data in this qualitative study. The paper found out that person’s own actions are not totally responsible for his failure, however human nature has significant role in changing their life too. Besides, the paper observes that nature, however unseen, dominates over all aspects of human life. The paper opens up the new ways of knowledge in the mainstream studies.